Report of the FAO/WorldFish Center Workshop on Interdisciplinary Approaches to the Assessment of Small-Scale Fisheries : (Food and Agirculture Organization of the United Nations, 2005)
The Workshop was organized jointly by the WorldFish Center and FAO through its FishCode Program, as a first step in developing a collaborative project towards capacity-building for small-scale fisheries assessment in developing countries. The Workshop addressed three main tasks through plenary and working group sessions: preliminary development of a framework for interdisciplinary assessment of small-scale fisheries; identification of appropriate approaches, methods and research needs to help fill small-scale fisheries information gaps; and review of an outline implementation strategy for a collaborative project on small-scale fisheries.